IMPACT OF SOCIAL MEDIA ON YOUTH MENTAL HEALTH IN CHENNAI CITY: AN EMPIRICAL STUDY (International Journal of Food and Nutritional Sciences, 2023)
In the past decade, social media has become an integral part of youth culture, especially in urban centers like Chennai. While platforms such as Instagram, WhatsApp, YouTube, and Snapchat provide avenues for communication, entertainment, and information, concerns regarding their influence on mental health have intensified. This study investigates the relationship between social media usage patterns and mental health indicators—namely anxiety, depression, self-esteem, and sleep quality—among youth aged 15–24 in Chennai City. Using a mixed-methods approach, data were collected from 300 survey respondents and 20 interview participants. Quantitative analysis revealed significant correlations between heavy usage and increased anxiety and depression scores, alongside lower self-esteem and poorer sleep quality. Qualitative insights highlighted both negative aspects, such as online harassment and social comparison, and positive aspects, such as emotional support and awareness of mental health campaigns. Findings emphasize the need for digital literacy programs, mental health awareness initiatives, and balanced usage guidelines to safeguard youth well-being.